Changes in isokinetic muscle strength of the knee in elite female adolescent volleyball players after 4 years of systematic training - Cheng, L.; Xu, H.; He, B.; Zhou, J. (Medicina dello Sport, 2021)
BACKGROUND: There are few reports regarding changes in joint muscle strength in elite-level adolescent athletes after systematic training.